Pengembangan Media Pembelajaran Berbasis Whatsapp dengan Fitur Chatbot untuk Meningkatkan Pemahaman Siswa pada Materi Kebijakan Moneter dan Fiskal Kelas XI SMAS Islam Nurul Amanah - Ahmad Izzat Makki; Ika Lis Mariatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this development research is to produce a whatsapp-based learning media product with a chatbot feature to improve students' understanding of monetary and fiscal policy materials. SMAS Islam Nurul Amanah Class XI is the subject of this study. In this study, a type of development research (Development Research) is used. The development model in this study uses the ADDIE development model. This model consists of five main phases or stages, namely Analysis, Design, Development, Implementation, and Evaluation. In this study, quantitative and qualitative methods are used. The results of the study showed that the whatsapp-based learning media with the chatbot feature was considered quite valid based on the results of a questionnaire filled out by material validators with a score of 70%, media validators with a score of 78%, and obtained a very valid assessment from economic learning practitioners with a score of 87%. Based on the results of validation and field trials, whatsapp-based learning media with a chatbot feature that has been developed by researchers is feasible to be used in the learning process in economics lessons, especially in monetary and fiscal policy material for grade XI of SMAS Islam Nurul Amanah.